Evaluating the predicting power of ordered probit models for multiple business cycle phases in the U.S. and Japan - Christian R. Proa\~no; Artur Tarassow (Institut für Makroökonomie und Konjunkturforschung (IMK), Hans-Böckler-Stiftung, 2017)
We investigate the probability forecasting performance of a three-regime dynamic ordered probit model framework suitable to forecast recessions, low growth periods and accelerations for the U.S. and Japan. In a first step, we apply a non-parametric dating algorithm for the identification of these three phases. We compare the pseudo-out-of-sample forecasting skills of an otherwise standard binary dynamic probit model with a three-regime dynamic ordered probit framework by means of a rolling-window exercise combined with time-varying indicator selection. Based on a set of monthly macroeconomic and financial leading indicators, the results show the superiority of the ordered probit framework to forecast all three business cycle phases up to six months ahead under real-time conditions. Apart from standard probability forecast evaluation measures, receiver-operating curves and related summarizing statistics are computed. – – Wir untersuchen die Prognosegüte eines dynamischen Ordered-Probit Modells mit drei Regimen hinsichtlich der Eintrittswahrscheinlichkeiten von Rezessionsphasen, Phasen niedrigen Wachstums sowie Boomphasen für die USA und Japan. Zuerst werden diese drei Regime mit Hilfe eines nicht-parametrischen Datierungsansatzes bestimmt. Die Prognosegüte eines gewöhnlichen binären dynamischen Probitmodells wird dann mit den Prognoseleistungen des dynamischen Ordered-Probit Modells mit drei Regimen verglichen. Diese Pseudo-Prognosen werden im Rahmen eines rollierenden Stützzeitraums inklusive einer automatischen Variablenselektionsprozedur generiert. Basierend auf monatlichen Beobachtungen makroökonomischer- und Finanzmarktvariablen, werden deutliche Hinweise für die Prognoseüberlegenheit des Ordered-Probit Modells für alle drei Regime bis zu einem Prognosehorizont von 6 Monaten sichtbar. Neben gewöhnlichen Evaluationsstatistiken für Wahrscheinlichkeitsprognosen werden die sog. Receiver-Operating-Characteristic (ROC) Kurve sowie zwei dazugehörige statistische Maße berechnet.
urn:nbn:de:101:1-201802215816
Keywords: C52; C53; C37; 330; Forecasting; Recession; Stagnation; ROC